THE EFFECT OF THE APPLICATION OF 20% CARBAMIDE PEROXIDE ON THE GLASS IONOMER CEMENT TYPE II SURFACE HARDNESS - Ali Noerdin; Chitra Mariani; Andi Soufyan (Faculty of Dentistry, Universitas Indonesia, 2015)
In dental bleaching, carbamide peroxide is usually used at concentration of 10%, 15%, to 20%. The result of our previous study showed that the application of 10% and 15% carbamide peroxide bleaching agent has increased the surface hardness of glass ionomer cement. The purpose of this study was to observe the effect of 20% carbamide peroxide bleaching to glass ionomer surface hardness. Twenty specimens of glass ionomer type II after exposed to 20% carbamide peroxide were divided into two application time groups: 4 and 8 hours per day. Glass ionomer cement surface hardness was measured by Vickers Microhardness Tester series HMV-2 with a weight of 0,025 Hv for 20 seconds. The measurement was conducted at before/no application, after a week, and after 2 weeks of application in both groups. It can be concluded that the application of 20% carbamide peroxide bleaching agent could increase the surface hardness of glass ionomer cement after 1 week and 2 weeks application period.